A new record of Schendyloides alacer (Pocock, 1891) from the Falkland Islands and a redescription of the species (Chilopoda Geophilomorpha) - Pereira, Luis Alberto (1993)
Fil: Pereira, Luis Alberto. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina